Transformation of the welfare state in New Zealand with special reference to employment : a thesis presented in partial fulfilment of the requirements for the degree of the Doctor of Philosophy in Economics at Massey University - De Bruin, Anne Marguerite (Massey University, 1997)
This study examines the transformation of New Zealand's welfare state in the movement to a new phase of capitalist development. It adopts a multi-level approach linking the global, national and local levels. The global level analysis provides the overall rationale for the development and subsequent restructuring of welfare states and reordering of the welfare mix more toward the market. At the national level, highlighting the collapse of its foundations, this study contends that New Zealand's welfare state has transformed into a 'well-being enabling state'. The goal of the well-being enabling state is to ensure private provision of welfare through labour market participation in a deregulated labour market, rather than through direct state provision. Employment policy, including policies for enhancement of human capital, are therefore discussed as 'enablers' of participation in paid employment and private procurement of well-being. At the local level, specific characteristics of the local labour market have to be included in the analysis. The need for community action for employment creation in order to respond to the challenges of the global economy and a transformed national welfare state, is a major theme of the study. A case study of community employment creation, conducted through a participatory research methodology, highlights the need for innovative local efforts for job creation at the micro or grassroots level. Local employment initiatives, especially those that build on a partnership approach and tap into the cultural wealth of the community through market-leading community entrepreneurship, are shown to be crucial to the mitigation of the current ethnic unemployment problem in New Zealand.
Keywords: Welfare state; Public welfare; Job creation; Minorities; Employment; Entrepreneurship; New Zealand